Awesome experiments in force & motion - Dispezio, Michael A.; Leary, Catherine (New York : Sterling, 1998)
Provides more than fifty experiments illustrating the properties of force and motion including gravity, inertia, and density.
Includes index.
School Library Journal.
3.8.
3.8
5-8
Keywords: Force and energy -- Experiments -- Juvenile literature; Motion -- Experiments -- Juvenile literature; Experiments; Force and energy -- Experiments; Motion -- Experiments; Force and energy -- Experiments; Motion -- Experiments; Science -- Experiments